Inhibiting neddylation: A new strategy for tumor therapy - Jian Sun; Cui Liu; Changhui Lang; Jing Wang; Qingxiang Li; Chang Peng; Zuochen Du; Yan Chen; Pei Huang (Journal of Pharmaceutical Analysis)
Neddylation is a crucial posttranslational modification that involves the attachment of neural precursor cell-expressed developmentally downregulated protein 8 (NEDD8) to a lysine residue in the substrate via the sequential actions of the E1 NEDD8-activating enzyme (NAE) (E1), E2 NEDD8-conjugating enzyme (E2), and E3 NEDD8-ligase (E3). The most extensively studied substrates of neddylation are members of the cullin family, which act as scaffold components for cullin ring E3 ubiquitin ligases (CRLs). Since cullin neddylation activates CRLs, which are frequently overactive in tumors, inhibiting neddylation has emerged as a promising strategy for developing novel antitumor therapies. This review explores the antitumor effects of inhibiting neddylation that leads to the inactivation of CRLs and provides a summary of known inhibitors that target protein-protein interactions (PPIs) within the neddylation enzymatic cascade.